The paradox of liberalization – Understanding dualism and the recovery of the German political economy - Anke Hassel (London School of Economics and Political Science (LSE), European Institute, 2011)
What do the recent trends in German economic development convey about the trajectory of change? Has liberalization prepared the German economy to deal with new challenges? What effects will liberalization have on the coordinating capacities of economic institutions? This paper argues that coordination and liberalization are two sides of the same coin in the process of corporate restructuring in the face of economic shocks. Firms seek labour cooperation in the face of tighter competitive pressures and exploit institutional advantages of coordination. However, tighter cooperation with core workers sharpened insider-outsider divisions and were built upon service sector cost cutting through liberalization. The combination of plant-level restructuring and social policy change forms a trajectory of institutional adjustment of forming complementary economic segments which work under different rules. The process is driven by producer coalitions of export-oriented firms and core workers' representatives rather than by firms per se.
Keywords: 330; Varieties of Capitalism; institutional change; labour market; industrial relations